2023
DOI: 10.21203/rs.3.rs-2346136/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlates of COVID-19 Vaccination Intentions and opinions about mandates among four groups of adults in South Africa with distinct vaccine intentions: Evidence from a large national survey

Abstract: Introduction Despite a high number of recorded COVID-19 infections and deaths in South Africa, COVID-19 vaccine coverage remained low in March 2022, ten months into the national vaccine roll-out. This study provides evidence on the correlates of vaccine intentions, attitudes towards vaccination and opinions about mandates. Methods We used data from the second COVID-19 Vaccine Survey (CVACS), a telephone survey conducted February-March 2022 among 3,608 South African adults who self-reported not being vaccinated… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…In seeking to understand these low vaccine uptake rates, this study identified two strong positive proximal predictors of vaccine acceptance: living in households where others had already been vaccinated, and knowing someone who had had COVID-19-a relative rarity in the setting. The household clustering of vaccine acceptance aligns with evidence from a South African national telephone survey in the same period [24], while a hesitancy-reducing effect of knowing someone with COVID-19 (especially severe cases) has been seen elsewhere including in Africa [25][26][27]. Notably, the effect of living with vaccinated household members did not appear to be a function of co-habitation with people vulnerable to COVID-19, since this association was independent of household member age.…”
Section: Plos Global Public Healthsupporting
confidence: 67%
“…In seeking to understand these low vaccine uptake rates, this study identified two strong positive proximal predictors of vaccine acceptance: living in households where others had already been vaccinated, and knowing someone who had had COVID-19-a relative rarity in the setting. The household clustering of vaccine acceptance aligns with evidence from a South African national telephone survey in the same period [24], while a hesitancy-reducing effect of knowing someone with COVID-19 (especially severe cases) has been seen elsewhere including in Africa [25][26][27]. Notably, the effect of living with vaccinated household members did not appear to be a function of co-habitation with people vulnerable to COVID-19, since this association was independent of household member age.…”
Section: Plos Global Public Healthsupporting
confidence: 67%